Review—Recent Development of WO3 for Toxic Gas Sensors Applications. Issue 10 (8th October 2021) - Bonardo, Doli; Septiani, Ni Luh Wulan; Amri, Fauzan; Estananto,; Humaidi, Syahrul; Suyatman,; Yuliarto, Brian
Abstract : WO3 -based gas sensors have attracted the attention of researchers around the world in creating and developing sensors that are sensitive, stable, and have excellent reproducibility against harmful gases. Various studies that have been performed since the last few years exhibited the superior potential of WO3 in carrying out optimal chemisorption of oxidizing and reducing gas molecules. The additional materials such as metal, metal oxide, and carbon nanomaterial can significantly widen the active state area of the WO3 surface and other facts in various studies illustrate that the addition of polymers will change the characteristics of the semiconductor sensor. This review provides a comprehensive review of the development and modification of WO3 for enhancing toxic gas sensor performances. In addition, the discussion of the sensing mechanism, future opportunities as well as challenges will be addressed thereby can inspire research progress on WO3 -based toxic gas detection sensors.